Jazz day : the making of a famous photograph - Orgill, Roxane (Candlewick Press, 2019)
Presents a poem for each of the jazz musicians included in the now-iconic 1958 "Esquire" magazine photograph known as "Harlem 1958," with musicians such as Milt "Fump" Hilton, William "Count" Basie, Thelonius Monk, and Maxine Sullivan.